Absorption of xylose, glucose, glycine, and folic (pteroylglutamic) acid in Zambian Africans with anaemia. Issue 8 (August 1976) - Cook, G C
Abstract : Rates of glucose, glycine, and folic (pteroylglutamic) acid absorption were determined for a 30 cm jejunal segment in vivo, with a double-lumen tube perfusion system, in 10 Zambian African women with a mean haemoglobin concentration of 5-1 (3-5-9-2) g/dl. In four the anaemia was megaloblastic (due to folate deficiency) and in six hypochromic. Perfusion solutions contained (1) glucose 200 mmol/1, (2) glycine 100 mmol/1, and (3) folic acid 250 mug/1. D-xylose absorption after a 25 g oral load was determined in them, and also in 18 additional patients (11 had megaloblastic and seven either hypochromic or haemolytic anaemia). Xylose absorption tests were significantly impaired in the patients with megaloblastic compared with hypochromic or haemolytic anaemia (P less than 0-001); those with untreated megaloblastic anaemia had a greater abnormality than those who had started treatment. Mean glucose, glycine, and folic acid absorption rates were similar to those in controls, and the rates in patients with megaloblastic and hypochromic anaemia were not significantly different. Correlation between glucose absorption rate and xylose excretion was, however, significantly (P less than 0-02). If more patients had been studied it seems likely therefore that a significant impairment of glucose absorption rate in the presence of megaloblastic anaemia would also have been demonstrated. In this investigation anaemia per se did not affect glucose, glycine, or folic acid absorption rates or xylose absorption, but xylose absorption was reduced in patients with megaloblastic anaemia. That abnormality was probably related to folate deficiency, and the underlying mechanism seems to be different from that causing impairment of monosaccharide absorption in patients with systemic bacterial infections. Mean glycine and folic acid absorption rates were not altered by megaloblastic anaemia, indicating that folate deficiency does not cause a general depression of absorption.